Intraoperative microelectrode recording under general anesthesia guided subthalamic nucleus deep brain stimulation for Parkinson's disease: One institution's experience - Qian, Kang; Wang, Jiajing; Rao, Jing; Zhang, Peng; Sun, Yaqiang; Hu, Wenqing; Hao, Jie; Jiang, Xiaobing; Fu, Peng (Frontiers in Neurology, 2023)
Objective Microelectrode recording (MER) guided subthalamic nucleus deep brain stimulation (STN-DBS) under local anesthesia (LA) is widely applied in the management of advanced Parkinson's disease (PD). Whereas, awake DBS under LA is painful and burdensome for PD patients. We analyzed the influence of general anesthesia (GA) on intraoperative MER, to assess the feasibility and effectiveness of GA in MER guided STN-DBS. Methods Retrospective analysis was performed on the PD patients, who underwent bilateral MER guided STN-DBS in Wuhan Union Hospital from July 2019 to December 2021. The patients were assigned to LA or GA group according to the anesthetic methods implemented. Multidimensional parameters, including MER signals, electrode implantation accuracy, clinical outcome and adverse events, were analyzed. Results A total of 40 PD patients were enrolled in this study, including 18 in LA group and 22 in GA group. There were no statistically significant differences in patient demographics and baseline characteristics between two groups. Although, the parameters of MER signal, including frequency, inter-spike interval (ISI) and amplitude, were obviously interfered under GA, the waveforms of MER signals were recognizable and shared similar characteristics with LA group. Both LA and GA could achieve effective electrode implantation accuracy and clinical outcome. They also shared similar adverse events postoperatively. Conclusion GA is viable and comparable to LA in MER guided STN-DBS for PD, regarding electrode implantation accuracy, clinical outcome and adverse events. Notably, GA is more friendly and acceptable to the patients who are incapable of enduring intraoperative MER under LA.